The Role and Strategy of Community Development for Elderly Families in Encouraging the Independence of Older People in Cianjur - Rahmayani, Octria; Emi, Chiara; Sulistiono, Eko (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
ABSTRACTThis research aims to explore and understand the role and strategies of the Elderly Family Development community in encouraging the independence of older people in Cianjur City. The Cianjur City Elderly Family Development Community has a vital role in encouraging the independence of older people. BKL not only acts as a place of socialization for older people but also as a place where they can get support, gain knowledge, and be involved in various activities that increase their independence. Data collection techniques using interviews and documentation. The Elderly Family Development Community has eight strategies: Providing Education and Information, Skills Development, Building Social Support, Holistic Approach, Organizing Recreational and Cultural Activities, Empowerment through Active Participation, collaboration and advocacy. Through these programs and activities, we can encourage older people to develop themselves, especially their independence. Therefore, the importance of collaboration with health services and local government emphasizes that the Elderly Family Development community does not stand alone. Keywords: Elderly Independence, Elderly Family Development Community